6S IMPLEMENTATION, DEVELOPMENT AND MEASUREMENT IN PROCESS INDUSTRY - Mattila, Lotta (My University, 2019)
The study is made to a company operating in the field of consumer goods. The target areas are in the company´s factory in process industry. The company have been working with lean with the focus on 6S. The 6S process made in the company is presented in the thesis. The main theories used are in the field of continuous improvement and employee empowerment. The research questions were 1. How to adopt the 6S methodology as a part of the factory culture? 2.What kind of measuring methods can be used to get the improvement to numeric form? 3. How to get people involved? and 4. How to sustain the reached levels and drive continuous improvement? The study was made as qualitative study and using observation method together with contextual inquiry. To support the findings also benchmarking method was used. The data was collected during a time period of 9 months in the case company by photographing target areas and communicating with the employees. Text of the abstract. The study showed that the 6S progress had affected the way employees work in the company and how they see the working environment. The idea of continuous improvement was adopted to most of the tar-get areas in the company. The study showed also future research ideas for other continuous improvement and lean methods.
Keywords: 6S Implementation, Lean Measurement, Process Industry, Kaizen, Observation, Contex-tual Inquiry, Benchmarking; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management